A new sequence data set of SSU rRNA gene for Scleractinia and its phylogenetic and ecological applications. (23rd January 2017) - Arrigoni, Roberto; Vacherie, Benoît; Benzoni, Francesca; Stefani, Fabrizio; Karsenti, Eric; Jaillon, Olivier; Not, Fabrice; Nunes, Flavia; Payri, Claude; Wincker, Patrick; Barbe, Valérie
Abstract: Scleractinian corals (i.e. hard corals) play a fundamental role in building and maintaining coral reefs, one of the most diverse ecosystems on Earth. Nevertheless, their phylogenies remain largely unresolved and little is known about dispersal and survival of their planktonic larval phase. The small subunit ribosomal RNA (SSU rRNA) is a commonly used gene for DNA barcoding in several metazoans, and small variable regions of SSU rRNA are widely adopted as barcode marker to investigate marine plankton community structure worldwide. Here, we provide a large sequence data set of the complete SSU rRNA gene from 298 specimens, representing all known extant reef coral families and a total of 106 genera. The secondary structure was extremely conserved within the order with few exceptions due to insertions or deletions occurring in the variable regions. Remarkable differences in SSU rRNA length and base composition were detected between and within acroporids ( Acropora, Montipora, Isopora and Alveopora ) compared to other corals. The V4 and V9 regions seem to be promising barcode loci because variation at commonly used barcode primer binding sites was extremely low, while their levels of divergence allowed families and genera to be distinguished. A time‐calibrated phylogeny of Scleractinia is provided, and mutation rate heterogeneity is demonstrated across main lineages. The use of this data set as a valuable reference for investigating aspects of ecology, biology, molecular taxonomy and evolution of scleractinian corals is discussed.